Helminth parasite communities of two Physalaemus cuvieri Fitzinger, 1826 (Anura: Leiuperidae) populations under different conditions of habitat integrity in the Atlantic Rain Forest of Brazil - Aguiar, A. [UNESP]; Toledo, G. M. [UNESP]; Anjos, L. A. [UNESP]; Silva, R. J. [UNESP] (Int Inst Ecology, 2015)
Adults of Physalaemus cuvieri were collected and necropsied between November 2009 and January 2010. This was carried out in order to report and compare the helminth fauna associated with two populations of this anuran species from the Brazilian Atlantic rain forest under different conditions of habitat integrity. The hosts from the disturbed area were parasitized with five helminth taxa: Cosmocerca parva, Aplectana sp., Physaloptera sp., Rhabdias sp., Oswaldocruzia subauricularis (Nematoda) and Polystoma cuvieri (Monogenea) while those from the preserved area had four helminth taxa: C. parva, Aplectana sp., Physaloptera sp., Rhabdias sp., and Acanthocephalus saopaulensis (Acanthocephala). Prevalence, mean intensity of infection, mean abundance, mean richness, importance index and dominance frequency of helminth component communities were similar in both areas. The helminth community associated with anurans from the disturbed area had higher diversity than that from the preserved area. This study is the first to report on the acanthocephalan parasites of Ph. cuvieri, and the similarity between helminth fauna composition of two host populations under different selective pressures.
Keywords: amphibian; Atlantic Rain Forest; component community; helminth fauna; parasites